LOS LECHEROS ANTIGUOS ESTÁN DE VUELTA: una iniciativa de marketing de la nostalgia con valor social de Danlac - Cesti Palomino, Alexandra (2020)
The present study focuses on one of the most representative campaigns of Danlac company: the return of the ancient dairy farmers, a project that the company materializes hiring elderly people. With that, Danlac manages to merge the concepts of emotional marketing and social marketing to generate value in an interdirectional way: for the company, customers and the new generation of dairy farmers that can be found in many supermarkets around the city. For the purpose of the analysis, the concepts of emotional marketing and social marketing will be defined. Subsequently, a description of the initiative will be made from the perspective of the concepts before mentioned which will include the dynamics of the project and the positive effects of the actors involved in it. Finally, the conclusion and the recommendations of the study will be presented, that will help to stand out and encourage other organizations to apply similar models.